SWOT ANALYSIS AND MARKETING STRATEGY TO INCREASE HOME BUSINESS SALES VOLUME - Asrida Asrida; Mai Simahatie; Elfiana Elfiana; Zahraini Zahraini; Denny Sumantri Mangkuwinata (Jurnal Ekonomi, 2022)
This research was conducted to analyze marketing strategies in an effort to increase sales volume of home-based businesses located in Matangglumpangdua, Paya Cut, Kec. Peusangan, Bireuen Regency. The research method used is descriptive method with a qualitative approachthe data analysis technique used is SWOT analysis, where this SWOT analysis is an internal and external analysis of a business or business. Internal analysis consists of analyzing the strengths and weaknesses of a business while external analysis consists of analyzing business opportunities and threats. Data collection is done by in-depth interviews with business or business owners. The results of the study show that this home-based business has not implemented an optimal marketing strategy which can be seen from the many deficiencies and threats identified. Thus, the solutions offered to increase the volume of sales of home-based businesses are to provide a special place for business (opening a shop), continuous and more production, registering a business and building partnerships.